BUILD SPACE LEARNING MEDIA INNOVATION CUBE AND BEAMS - Yuli Arista Sarumingsari; Dwi Kameluh Agustina; Ida Putri Rarasati (Universitas Islam Balitar, 2019)
Based on observations made in the wake of material math learning space, found a tedious learning process, learners are not active, the method used monotonous and unattractive instructional media, and therefore contributes to the understanding of the material. Thus the researchers aim to produce instructional media such as wake-up room is equipped with an image of objects around the expected with the media learners do not feel bored and active in learning and better understand the material got up space, determine the feasibility of the product, know the response of the students to the product produced. The research conducted is research the development of R & D (Research and Development). Results from these studies is the acquisition of the results of validation of materials experts 95.67%, 86.67% of media experts, and the acquisition of the validation results linguists 91.30% of the validation results of this third entry in the media very worthy qualification does not need to be revised. Thus, the product is fit for use as a learning medium grade elementary school mathematics. Based on the results of the acquisition of the response of learners to answer